The C-terminus region of β-arrestin1 modulates VE-cadherin expression and endothelial cell permeability - Hebda, Jagoda K (BioMed Central, 2013)
BACKGROUND: The endothelial specific cell-cell adhesion molecule, VE-cadherin, modulates barrier function and vascular homeostasis. In this context, we have previously characterized that VEGF (vascular endothelial growth factor) leads to VE-cadherin phosphorylation, β-arrestin2 recruitment and VE-cadherin internalization in mouse endothelial cells. However, exactly how this VE-cadherin/β-arrestin complex contributes to VEGF-mediated permeability in human endothelial cells remains unclear. In this study, we investigated in-depth the VE-cadherin/β-arrestin interactions in human endothelial cells exposed to VEGF. FINDINGS: First, we demonstrated that VEGF induces VE-cadherin internalization in a clathrin-dependent manner in human umbilical vein endothelial cells (HUVEC). In addition to the classical components of endocytic vesicles, β-arrestin1 was recruited and bound to phosphorylated VE-cadherin. Molecular mapping of this interaction uncovered that the C-terminus tail of β-arrestin1, that comprises amino acids 375 to 418, was sufficient to directly interact with the phosphorylated form of VE-cadherin. Interestingly, the expression of the C-terminus tail of β-arrestin1 induced loss of surface exposed-VE-cadherin, promoted monolayer disorganization and enhanced permeability. Finally, this effect relied on decreased VE-cadherin expression at the transcriptional level, through inhibition of its promoter activity. CONCLUSIONS: Altogether, our results demonstrate that β-arrestin1 might play multiple functions collectively contributing to endothelial barrier properties. Indeed, in addition to a direct implication in VE-cadherin endocytosis, β-arrestin1 could also control VE-cadherin transcription and expression. Ultimately, understanding the molecular mechanisms involved in VE-cadherin function might provide therapeutic tools for many human diseases where the vascular barrier is compromised.